Desmercantilização da habitação: entre a luta e a política pública - Marina Sanders Paolinelli (2018)
This work aims to investigate the transformation of housing into a commodity and the efforts made against this process, mobilized by the dialogue between the housing struggles and the State in the elaboration of public policies. The approach adopted follows the perspective of the political economy and seeks to highlight the role of the housing sector in the perspective of capital, State and anti-capitalist struggles. With the purpose of analyzing the housing problem from a broad point of view, the work puts in dialogue authors who investigate Brazilian housing policy, informality and the production of housing in the peripheral context, foreign authors dealing with the housing policy of their contexts and developing relations between countries of central capitalism, and transverse authors, who break the barriers between the global north and south in their texts. Thus, the paper seeks to contextualize the housing problem in the face of the emergence of neoliberalism, privatization, financialization and precarization of housing systems in the global context and, at the same time, give due attention to the peculiarities of this process in the Brazilian context, taking into account the informality, the growth of the periphery and the forms of housing struggles. Considering the State as a field of forces, the work investigates the state performance in the housing sector in emblematic contexts in global history, which both favored and created alternatives to the process of commodification of housing. Comparing these experiences, based maily in social rent policies, with the Brazilian State action in the housing sector, focused in the housing mass production and the mitigation of informality, the work seeks to analyze possibilities and impossibilities of decommodification of housing in the Brazilian context. Seeking to converge the reflections of the national and international literature collected and link a theoretical reflection with a more purposeful approach, the work concludes tracing possible ways of State action towards a housing system that treats housing less as a commodity, and more like a right. In this sense, it brings, in addition to the debates between national and international literature, recent debates and discussions promoted in Belo Horizonte by the Coletivo Habite a Política, an initiative of a group of activist technicians with social movements, professional entities and research groups academics.